Inventário de emissões de gases de efeito estufa de fabricante de computadores - Nagal, Fernanda Valentim (2010)
Several initiatives are being developed and implemented which aim to limit the emissions of greenhouse gases (GHG) into the atmosphere. A GHG inventory is a “snapshot” of the emissions caused by the activities of a certain organization. Development and maintenance of the inventory allows a company to identify sources and quantify emissions, and, thus, define reduction and compensation strategies. The development of the GHG inventory of the company subject of the work reported herein, a computer manufacturer, was based on the GHG Protocol guidelines, following the principles of relevance, completeness, consistency, transparency and accuracy. The base year was 2008, and the inventory encompassed the company's activities carried out at the Curitiba units. All sources of emissions of greenhouse gases identified were included in the inventory. After the emissions were calculated, comparisons were made with inventories published by participants of the Brazilian GHG Protocol program, and other computer manufacturers, which established the need for identification of emission sources in each scope to allow comparisons between different organizations. It was concluded that the largest emissions generated in the life cycle of a computer arise from extraction of raw materials, transportation of imported components, and energy consumption during use, all framed within scope 3. It was found that for comparisons of inventories the discrimination of sources inventoried in scope 3 is fundamental. These comparisons also showed that the emissions profile of the inventory reported herein is different from those of organizations outside the country, since their emissions in scope 2 are significantly higher than in Brazil, due to the differences in electricity production at each country. The main uncertainties associated with emission estimates are activity data and emission factors.